Context Matters: Economic Voting in the 2009 and 2014 European Parliament Elections - Okolikj, Martin (2016)
Using the 2009 and 2014 European Election Studies (EES), we explore the effect of the economy on the vote in the 2009 and 2014 European Parliament (EP) elections. The paper demonstrates that the economy did influence voters in both contests. However, its impact was heterogeneous across the two elections and between countries. While assessments of the economy directly motivated voters in 2009 by 2014 economic appraisals were conditioned by how much responsibility voters felt the national government had for the state of the economy, implying a shift in calculus between the two elections. The analysis suggests that voters in 2009 were simply reacting to the economic tsunami that was the Global Financial Crisis, with motivations primarily driven by the unfavourable economic conditions countries faced. But in 2014, evaluations were conditioned by judgments about responsibility for the economy, suggesting a more conscious holding to account of the government. Our paper also reveals cross-country differences in the influence of the economy on vote. Attribution of responsibility and economic evaluations had a more potent impact on support for the government in bailout countries compared to non-bailout countries in 2014. Our findings demonstrate the importance of economy on vote in EP elections but also highlight how its impact on vote can vary based on context.